Business Character Implementation Strategy for The Community of Teluk Patipi District - Atarai Iba; Sri Rahayu; Angky Soedrijanto; Yohana Dina Hindom (Journal of Business Innovation and Accounting Research, 2024)
This research focuses on evaluating the preparedness of the inhabitants of Patipi Pasir village and its vicinities within the East Fakfak district to cultivate their entrepreneurial spirit. The pivotal aim is to harness their potential in managing local natural resources effectively, thereby contributing significantly to the economic acceleration of the Fakfak district. Employing a descriptive research methodology, the study uses a semi-qualitative analysis and a fishbone diagram to identify areas requiring improvement. Moreover, the strategic implementation for nurturing business character among the local populace is devised through the innovative use of the Ishikawa diagram, integrated with the Balanced Scorecards approach, providing a comprehensive development framework. The findings reveal that the Patipi Bay District boasts considerable human resource potential that, if adequately nurtured, can lead to the effective management of its natural resources into sustainable businesses. The study underscores the need to develop a robust entrepreneurial ecosystem that supports the local community's transition to sustainable economic practices. This entails providing adequate training, resources, and support systems to empower the community, ensuring they are well-equipped to capitalize on the intrinsic value of their natural resources. Through strategic planning and targeted development programs, the research envisions transforming the Patipi Bay District into a model for sustainable business development, leveraging its natural assets for long-term economic prosperity.